Young man with a horn [videorecording (DVD)] - Baker, Dorothy, 1907-1968; Day, Doris, 1922-2019-; Douglas, Kirk, 1916-2020-; Bacall, Lauren, 1924-2014; Carmichael, Hoagy, 1899-1981 (Warner Bros., 2017)
A lonely little boy peeks into the window of a Skid Row dive. Mesmerized by the soaring magic played by a small jazz combo, he longs to create the same sounds. So with the guidance of a brilliant bluesman, the boy develops into a superb artist.